Empowering Mothers in Training Active Eating in Children Aged 8-18 Months in Suka Maju Village, Mestong Muara Jambi District : Pemberdayaan Ibu dalam Melatih Makan Aktif pada Anak Usia 8-18 Bulan Di Desa Suka Maju Kecamatan Mestong Muara Jambi - Nuraidah; Netti Herawati (Yayasan Ahmar Cendekia Indonesia, 2024)
This high level of nutritional problems is an important problem that needs to be followed up, so that the impact of nutritional problems does not interfere with growth and development. Suka Maju Village has 15 malnourished babies and 59 undernourished babies, in 2022. This can result in stunting. In order for children's growth and development to run well, children must eat enough. One of the methods recommended by WHO-UNICEF is active/responsive feeding techniques. The aim of community service is to increase mothers' knowledge and skills in actively feeding their children. The target of community service is 20 mothers and 5 cadres. This activity was carried out in Suka Maju village, Mestong District, Muaro Jambi Regency. The method of this activity is socialization of materials and education/demonstration of how to wash hands and actively feed children. After the socialization activities were carried out, there was an increase in mother's knowledge before with an average of 4.9 and after an average of 9.06 socialization of 4.15. There was an increase in cadre knowledge with an average of 6.4 before and after 9.8. Increased by 3.4. And there was an increase in maternal skills before with a mean of 4.4 and after a mean of 12.9 an increase of 8.5. There was an increase in average cadre skills before 8.8 and after 14.0. Increased by 5.2. The conclusion is that there has been an increase in the knowledge and skills of mothers. With the help of partners, monitoring and sustainability needs to be done so that mothers can provide food and get children used to being independent in eating.